2000
DOI: 10.1136/adc.83.4.340
|View full text |Cite
|
Sign up to set email alerts
|

Tracheomalacia and breath holding: a case report

Abstract: A child with a long standing history of cyanotic breath holding attacks presented with acute respiratory distress. Subsequent investigation established that her clinical condition was caused by tracheomalacia. We hypothesise that tracheomalacia might be an under recognised contributor to cyanotic breath holding attacks, the pathogenesis of which is poorly understood. (Arch Dis Child 2000;83:340-341)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…88 Affected children may display noisy, medium-pitched to high-pitched breathing. In addition, recurrent respiratory distress, 36 wheezing, 21,89 cyanosis, 86 spontaneous hyperextension of the neck, 12,29,49,90 and breath-holding spells 91 have been reported. The "bagpipe sign," an expiratory sibilant note that persists after the end of visible expiration, also has been described.…”
Section: Symptomsmentioning
confidence: 99%
“…88 Affected children may display noisy, medium-pitched to high-pitched breathing. In addition, recurrent respiratory distress, 36 wheezing, 21,89 cyanosis, 86 spontaneous hyperextension of the neck, 12,29,49,90 and breath-holding spells 91 have been reported. The "bagpipe sign," an expiratory sibilant note that persists after the end of visible expiration, also has been described.…”
Section: Symptomsmentioning
confidence: 99%
“…Tracheomalacia is characterized by weakness in the tracheal wall due to softening of the supporting cartilage and hypotonia of myoelastic elements [ 13 , 15 ]. Causes of acquired tracheomalacia include trauma, surgery, chronic irritation, infection, mechanical changes, and malignant infiltration [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of tracheomalacia after thyroidectomy is estimated to be between 0.8 % and 5.8 %. Several studies have examined the risk of tracheomalacia as a respiratory complication following thyroidectomy [ 15 , 19 ]. A prospective study conducted by Rahim et al reported that 32 patients (31 %) experienced postoperative respiratory complications, and 13 of them required tracheostomy, and tracheomalacia was the most common indication (5 patients) [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Riwayat breath holding dapat terjadi; patogenesis terjadinya belum diketahui. 10 Pada pemeriksaan fisik, bayi dengan kelainan ini tampak dalam kondisi baik meski dengan mengi kronik. Tanda vital, termasuk laju respirasi dan saturasi oksigen normal.…”
Section: Manifestasi Klinisunclassified